Analisis Kinerja Keuangan Pemerintah Daerah Kota Tebing Tinggi : (Studi Kasus Pada Badan Pengelolaan Keuangan Dan Pendapatan Daerah Kota Tebing Tinggi) - Mutiara Octavia; Rahmi Syahriza; Nur Fadhilah Ahmad Hasibuan (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
This research aims to analyze the financial performance of the regional government of Tebing Tinggi City using the degree of fiscal decentralization ratio, regional financial independence ratio, regional financial dependency ratio, PAD effectiveness ratio, regional financial efficiency ratio, harmony ratio and growth ratio. This research uses a descriptive qualitative approach method. Data collection techniques include interviews and documentation obtained from budget realization reports. Based on the results of the financial ratio analysis, it shows that the degree of fiscal decentralization ratio is categorized as deficient with a range of 11.98%-15.89%. The regional financial independence ratio is classified as very low with a range of 14.32%-19.55% with an instructive relationship pattern. The regional financial dependency ratio is categorized as very high with a range of 78.91%-83.64%, where the percentage is more than 50%. The PAD effectiveness ratio is categorized as less effective in 2019, 2020 and 2022 with a range of 80.75%-88.35%. However, in 2018 it was categorized as very effective because it was more than 100%, namely 108.02%. Meanwhile, in 2021 it is categorized as ineffective because it is less than 75%, namely 70.05%. The regional financial efficiency ratio is categorized as less efficient in 2019-2021 with a range of 96.61%-99.10%. However, in 2018 and 2022 it is categorized as inefficient because it is more than 100%, namely 103.92% and 102.61%. The harmony ratio shows that the City of Tebing Tinggi prioritizes its funds towards operating expenditure with an average operating expenditure of 76.05% and a capital expenditure ratio of 23.45%. The growth ratio of PAD, regional income, operating expenditure and capital expenditure experienced positive and negative growth in the 5 budget years.